2014
DOI: 10.1093/aobpla/plt054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water availability and pest pressures on tea (Camellia sinensis) growth and functional quality

Abstract: Extreme shifts in water availability linked to global climate change are impacting crops worldwide. This study examines effects of water availability and pest pressures on the growth and functional quality of tea, the world's most consumed beverage after water. Results show that higher water availability and pest pressures significantly increased the growth of new leaves while their effect on tea quality varied with individual secondary metabolites. Findings point to the fascinating dynamics of climate change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…Farmers interviewed in Yunnan China confirm this finding; they believe tea quality varies by season and is especially affected by the arrival date of the East Asian Monsoon [18]. Another study in a controlled greenhouse environment found that tea grown with higher water availability had significantly lower concentrations of epigallocatechin 3-gallate, a flavonoid found in many teas that helps to drive quality of the consumable product [19]. Clearly, the monsoon rainfall plays a key role in plant growth and quality and harvesting decisions.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Farmers interviewed in Yunnan China confirm this finding; they believe tea quality varies by season and is especially affected by the arrival date of the East Asian Monsoon [18]. Another study in a controlled greenhouse environment found that tea grown with higher water availability had significantly lower concentrations of epigallocatechin 3-gallate, a flavonoid found in many teas that helps to drive quality of the consumable product [19]. Clearly, the monsoon rainfall plays a key role in plant growth and quality and harvesting decisions.…”
Section: Introductionmentioning
confidence: 81%
“…Farmers in Yunnan province report some other strategies to address changes in precipitation patterns. These include planting tea from seed instead of using clonal propugules which have less dense and deep root systems; mixed cropping of tea gardens in forests; and enhancing the drainage of tea gardens [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations